Antihyperglycemic Effect of Gymnema inodorum in Type 2 Diabetes Management - Watis Kongcharoen; Ananya Jaturaporn; Kittisak Chavalit; Nathirat Charoensup (Journal of Advances in Medicine and Pharmaceutical Sciences, 2024)
This study investigates the antihyperglycemic effects of Gymnema inodorum (Chiang Da), a traditional medicinal plant from northern Thailand, commonly used for managing blood glucose levels. The goal was to evaluate its pharmacological effects, including the inhibition of alpha-glucosidase and its ability to lower blood glucose levels in Type 2 diabetic rats. Ethanol maceration was used to extract bioactive compounds from Chiang Da leaves, yielding gymnemic acids, saponins, and flavonoids. The in vivo study involved administering Chiang Da tea to diabetic rats for 8 weeks, measuring fasting and postprandial blood glucose levels. Results showed a significant reduction in blood glucose levels in the Chiang Da-treated group, comparable to the synthetic drug metformin. In vitro tests also revealed the extract’s concentration-dependent inhibition of alpha-glucosidase, with an IC50 value of 45 µg/mL, indicating moderate potency in delaying glucose absorption. Descriptive and inferential statistics confirmed that Chiang Da tea significantly reduced blood glucose levels, though its effects were less pronounced than metformin’s. These findings support the potential of Chiang Da as a natural alternative for managing Type 2 diabetes, particularly for individuals seeking plant-based treatments. Future research should focus on clinical trials to further evaluate the efficacy and safety of Chiang Da for diabetes management, as well as explore its potential for combination therapy with conventional drugs to enhance therapeutic outcomes.